2021
DOI: 10.1177/02698811211064922
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent metabolism of ketamine and (2R,6R)-hydroxynorketamine in mice and humans

Abstract: Background: Ketamine is rapidly metabolized to norketamine and hydroxynorketamine (HNK) metabolites. In female mice, when compared to males, higher levels of ( 2R,6R;2S,6S)-HNK have been observed following ketamine treatment, and higher levels of ( 2R,6R)-HNK following the direct administration of ( 2R,6R)-HNK. Aim: The objective of this study was to evaluate the impact of sex in humans and mice, and gonadal hormones in mice on the metabolism of ketamine to form norketamine and HNKs and in the metabolism/elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 87 publications
4
12
0
Order By: Relevance
“…Proper comparisons of ketamine’s therapeutic and adverse effects in male and female patients are lacking, possibly due to the limited statistical power for such subgroup analysis in current clinical trials, although sex differences have previously been reported at an anecdotal level ( 51 ). Sex-dependent ketamine and norketamine pharmacokinetics have been observed ( 52 ), and diverging correlations between treatment outcomes and depression-related inflammatory cytokines have been reported in male and female subjects ( 53 ). Moreover, preclinical investigations showed sex differences in the pharmacokinetics of ketamine and its metabolites, as well as in behavioral and physiological readouts ( 12 , 52 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proper comparisons of ketamine’s therapeutic and adverse effects in male and female patients are lacking, possibly due to the limited statistical power for such subgroup analysis in current clinical trials, although sex differences have previously been reported at an anecdotal level ( 51 ). Sex-dependent ketamine and norketamine pharmacokinetics have been observed ( 52 ), and diverging correlations between treatment outcomes and depression-related inflammatory cytokines have been reported in male and female subjects ( 53 ). Moreover, preclinical investigations showed sex differences in the pharmacokinetics of ketamine and its metabolites, as well as in behavioral and physiological readouts ( 12 , 52 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sex-dependent ketamine and norketamine pharmacokinetics have been observed ( 52 ), and diverging correlations between treatment outcomes and depression-related inflammatory cytokines have been reported in male and female subjects ( 53 ). Moreover, preclinical investigations showed sex differences in the pharmacokinetics of ketamine and its metabolites, as well as in behavioral and physiological readouts ( 12 , 52 , 54 ). Our results represent a critical step forward in elucidating both sex-dependent and opioid-based mechanisms underlying the action of subanesthetic ketamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have documented the effect of OVX on the efficacy of various antidepressants (Estrada et al ., 2011; Ye et al ., 2016; Highland et al ., 2022). However, the results have not been conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Continuing the psychosis theme, Loureiro et al (2022) use the PCP model of schizophrenia in rats, to demonstrate effects on methylation and protein expression of NMDA receptor subunit genes in prefrontal cortex and hippocampus. In the final pre-clinical study, Highland et al (2021) examine whether metabolism of ketamine is sex-dependent, using both animal and human data. They found sex differences in mice and humans administered ketamine, with males of both species having higher levels of ketamine and one of its metabolites norketamine but higher levels of the other metabolite of ketamine, hydroxynorketamine, in female mice.…”
mentioning
confidence: 99%